The retreat - Pearse, Sarah (Pearse, Sarah. Detective Elin Warner, 2022)
"An eco-wellness retreat has opened on an island off the English coast, promising rest and relaxation--but the island itself, once the playground of a serial killer, is rumored to be cursed. Detective Elin Warner is called to the retreat when a young woman's body is found on the rocks below the yoga pavilion in what seems to be a tragic fall. But the victim wasn't a guest--she wasn't meant to be on the island at all. When a guest drowns in a diving incident the following day, Elin starts to suspect that there's nothing accidental about these deaths. Elin must find the killer--before the island's history starts to repeat itself"--